Design and Implementation of an IoT-Based Smart Attendance System - Michael R. ADU; Afeez O. OLAWUNMI (FUDMA Journal of Engineering and Technology, 2026)
In this paper, a smart attendance system designed on IoT with Radio Frequency Identification (RFID) technology has been implemented. The system helps resolve the inefficiencies of manual attendance management methods, including roll calls and paper registers that are time-consuming, error-prone, and easy to impersonate. It combines an RFID device (RC522), a microcontroller with Wi-Fi features (ESP32), and cloud-based solutions (Google Sheets and API) to automate classroom attendance and examination hall attendance. Every student will be given an RFID card in which the Unique Identifier (UID) is captured, processed, and logged in real time to a cloud database. The system was tested to correctly record attendance and update information to the cloud within approximately 2 seconds, run continuously with no failures, and achieve 98.9 percent uptime, with a positive user rating for speed and ease of use. Although the system had some minor drawbacks, such as a limited reading range, reliance on Wi-Fi, and the possibility of card duplication, it was an effective, cost-effective, and efficient alternative to manual attendance systems. The research finds that RFID and IoT technologies can significantly enhance transparency, accountability, and administrative efficiency at academic institutions.
Keywords: RFID, Smart Attendance System, Internet of Things (IoT), ESP32 Microcontroller, Google Sheet, Embedded Systems, Wireless Communication.